The relationship between cognitive flexibility and cognitive fusion with the borderline personality disorder symptoms - Hajitabar Firouzjaei , Nima; Soltani, Esmail; Dastgheib , Seyed Ali (Researcher Bulletin of Medical Sciences, 2021)
Since researches have shown that maladaptive cognition plays a role in the beginning and maintenance Borderline Personality Disorder (BPD), this research aims to evaluate the relationship between cognitive flexibility and cognitive fusion with borderline personality disorder symptoms. 356 students of Mazandaran University of Medical Sciences who studied in the academic year of 2017-2018 were selected using cluster sampling method and they completed Cognitive Flexibility inventory (CFI), Cognitive Fusion Questionnaire (CFQ) and Schizotypal Trait Questionnaires (STB). There was a positive and significant relationship between cognitive fusion and borderline personality disorder (BPD) (p<0.01). The correlation between cognitive flexibility and borderline personality disorder and subscales was significant and negative (p<0.01, p<0.05). Cognitive flexibility and cognitive fusion and their subscales can predict the BPD factors. It is suggested that psychological interventions, especially cognitive-behavior therapy (CBT) and Acceptance and Commitment Therapy (ACT), are used to increase the cognitive flexibility and reduce cognitive fusion of students with borderline personality symptoms